Amtsâl and Aqsâm in the Qur'an (Ulumul Qur'an) - Baldi Anggara (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
The Qur'an is a revelation sent down by Allah SWT. speak Arabic. It is the greatest miracle for the Prophet Muhammad SAW. The Qur'an applies throughout the ages until the Day of Judgment. As the laws contained therein apply, both textually and contextually. Al-Qur'an, a phenomenal holy book. Protected until the end of time, both written and read. It is a guide to life for Muslims and at the same time a guide for humans. Imam Baihaqî narrated the hadith from Abu Hurairah Ra. Hadith History of al-Baihaqî No. 2212. Based on this hadith, the Qur'an really needs to be studied. With in-depth study, good understanding will emerge, with the hope that a sense of awe and majesty will arise towards the Al-Qur'an, especially towards Allah SWT. who took it down. And it is hoped that they will be able to practice the messages contained in it. Something that is rarely studied is about amtsâl and aqsâm in the Koran. As Imam Al-Mâwardî said, among the greatest knowledge in the Qur'an is the knowledge of amtsâl, and most people are negligent and forget to study it. So in this paper we will present a study of amtsâl and aqsâm contained in the Al-Qur'an. With the problem formulation; What is the meaning of amtsâl and aqsâm? What type? And what are the benefits? The method used by the author is a qualitative method, which produces findings that cannot be achieved using statistical procedures or other methods of quantification. Even simpler is research that does not carry out calculations. Based on the area, this study can be classified as library research, which involves identifying and finding sources that provide factual information.